Neonatal neurological examination in a resource-limited setting: What defines normal?. (November 2020) - Lawford, Harriet L.S.; Nuamah, Mercy A.; Liley, Helen G.; Lee, Anne CC; Kumar, Sailesh; Adjei, Andrew A.; Bora, Samudragupta; ,; Samba, Ali; Adjei, Andrew A.; Lee, Anne CC; Badoe, Ebenezer V.; et al.
Abstract: Objective: To describe the results of the Hammersmith Neonatal Neurological Examination (HNNE) in a low-risk, term-born, contemporary sample in Ghana. Of particular interest was to compare these findings with the original British study that validated the HNNE, and published data from other low- and middle-income countries. Study design: In a nested substudy of a larger prospective study (IMPRINT: Impact of Malaria in Pregnancy on Infant Neurodevelopment), 140 low-risk, term-born neonates (39.3 ± 1.4 weeks gestation) at Korle Bu Teaching Hospital in Accra, Ghana were administered the 34-item HNNE from birth to 48 h of age by trained physicians. Neonates' performance was compared with previously published normative data from the United Kingdom (1998), and published data from Thailand, Myanmar, Vietnam, and Uganda. Results: Ghanaian neonates demonstrated lower scores on 29/34 HNNE items relative to normative data from the United Kingdom ( P < .05), with only 5% of Ghanaian neonates in our sample classified as neurologically optimal. There were significant differences in the proportion of neonates scoring optimally per HNNE item between our Ghanaian sample, compared with published data from other settings (Thai [13/16 items], Burmese [14/16 items], Vietnamese [7/9 items], and Ugandan [22/34 items] neonates). Raw scores were markedly different between Ghanaian and British neonates, with Ghanaian neonates demonstrating lower median and wider range of scores. These differences were less prominent between Ghanaian and Ugandan neonates. Conclusion: Our findings raise questions as to whether or not the thresholds for optimality for the HNNE based on data from the United Kingdom are applicable to Ghanaian newborns. Our study could not fully resolve whether the differences in scores were due to genetic differences in developmental pathways, the implementation of the assessment, or the characteristics of our sample. Low proportions of neonates scoring optimally from other low- and middle-income countries suggest the need for further research to determine the clinical utility of the HNNE in resource-limited settings, including the predictive value for neurodevelopment later in infancy. Highlights: Neonatal neurological profiles differ notably for high- and low-resource settings. Neonatal tone patterns are more consistent across high- and low-resource settings. Distinct cut-off scores for high- and low-resource settings will increase utility.